Disciplined or Punished? The Future of Graduate Education in Women's Studies - Caughie, Pamela L.; Parks, Jennifer A. (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
This article considers the ways in which graduate programs in women's studies and the students in those programs are challenged by the still-present emphasis on disciplinary training. It discusses some methodological, ethical, and programmatic questions associated with running graduate programs in women's studies, and some practical recommendations in response, ones that resist making a choice between either sustaining or abandoning women's studies programming.